The formation of prosociality: Causal evidence on the role of social environment - Fabian Kosse; Thomas Deckers; Hannah Schildberg-Hörisch; Armin Falk (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This study presents descriptive and causal evidence on the role of social environment for the formation of prosociality. In a first step, we show that socio-economic status (SES) as well as the intensity of mother-child interaction and mothers prosocial attitudes are systematically related to elementary school children's prosociality. In a second step, we present evidence on a randomly assigned variation of the social environment, providing children with a mentor for the duration of one year. Our data include a two-year follow-up and reveal a significant and persistent increase in prosociality in the treatment relative to the control group. Moreover, enriching the social environment bears the potential to close the observed developmental gap in prosociality between low and high SES children. Our findings suggest that the program serves as a substitute for prosocial stimuli in the family environment.
Keywords: D64; C90; 330; formation of preferences; prosociality; social preferences; trust; social inequality